lncRNA OIP5-AS1 Suppresses Cell Proliferation and Invasion of Endometrial Cancer by Regulating PTEN/AKT via Sponging miR-200c-3p - Yun Liu; Xiaohui Cai; Yixuan Cai; Yue Chang (Journal of Immunology Research)
Background. Endometrial carcinoma (EC) is one of the major gynecologic malignancy cancers affecting females with dismal prognosis and high mortality around the world. Numerous studies have proven that an aberrant level of long noncoding RNAs is present in many endometrial cancer patients, while the underlying molecular mechanism remains unclear. Method. The expression levels of lncRNA OIP5-AS1, miR200c-3p, and PTEN were measured by a quantitative real-time polymerase chain reaction in endometrial cancer tissue and endometrial cancer cells. CCK8 assay, wound-healing assay, and cell colony formation were applied to evaluate cell proliferation, cell migration, and cell colony formation ability. Cell cycle and cell apoptosis were detected by flow cytometry. The interactions between OIP5-AS1, miR200c-3p, and PTEN were explored by luciferase activity. Results. In the present study, we demonstrated that long noncoding RNA OIP5-AS1 was significantly reduced in EC tissue compared with normal tissue. The lower expression level of OIP5-AS1 was also confirmed in four kinds of EC cell lines compared with the normal endometrial cell line. Gain- and loss-of-function of experiments indicated that upregulation of OIP5-AS1 could inhibit the proliferation, migration, and invasion of EC cells in vitro. Meanwhile, overexpression of OIP5-AS1 could also suppress the growth of tumor in the xenograft model. Moreover, further study revealed that miR-200c-3p could bind to OIP5-AS1, and the loss function of miR-200c-3p could reverse the elevated OIP5-AS1’s inhibitory effect on the progression of EC. Furthermore, we found that downregulation of miR-200c-3p was inversely correlated with PTEN expression in EC cells. Reduced OIP5-AS1 could lead to the accumulation of miR-200c-3p, which could induce the upregulation of PTEN indirectly. Conclusion. Our study demonstrated a novel molecular mechanism that lncRNA OIP5-AS1 could modulate the progression of EC by combining competitively with miR-200c-3p to control the PTEN/AKT pathway in EC cells, which might supply important information for developing novel therapeutic strategies for EC patients.